A half century without a master: Do you want William Faulkner’s imagintation? - Sanz Barajas, Jorge (Razón y fe, 2018)
Last Junemarked the 50th anniversary of William Faulkner’s death (1897- 1962). Faulkner, the Mississippi poet, was together with Joyce a widely-quoted writer but barely read. Linked to his fascinating existence, we are offereda handful of keys in an effort of synthesis and courage to understand and like the «poet who wrote in prose», the writer who read and remained silent, andthe creator of the imaginary Yoknapatawpha, a fertile ground to know and love the human being.
Keywords: Faulkner; Mississippi; Yoknapatawpha